Clinical outcomes with high-dose-rate surface mould brachytherapy for intra-oral and skin malignancies involving head and neck region - Budrukkar, Ashwini; Dasgupta, Archya; Pandit, Prakash; Laskar, Sarbani Ghosh; Murthy, Vedang; Upreti, Ritu Raj; Gupta, Tejpal; Dholam, Kanchan; Agarwal, Jai Prakash (Journal of Contemporary Brachytherapy, 2017)
Purpose : The literature and experience of high-dose-rate (HDR) surface mould brachytherapy (SMB) in head and neck cancer is sparse. We report our institutional experience of SMB for such tumours. Material and methods: Thirty-five patients with malignant localized early T1/T2, N0 (21 intra-oral and 14 skin) tumours treated with SMB during 2008-2014 were analyzed. Treatment was delivered using HDR 192Ir source to a median dose of 49 Gy (range, 38.5-52.5 Gy) as radical brachytherapy and 18 Gy (range, 15.5-30 Gy) as boost with 3-4 Gy/fraction twice daily using customized surface mould. Results : Median follow-up was 52 months (range, 6 to 98 months). Local control (LC) for skin tumours and intra-oral malignancies at 5 years were 92% and 76%, respectively. Five-year cause specific survival was 92%. For T1 and T2 tumours, 5 year LC was 94.2% and 68.2%, respectively. T stage (p < 0.04) and dose/fractions (p < 0.003) were the only significant prognostic factors for LC on univariate analysis. Conclusions : Surface mould brachytherapy results in excellent LC rates for skin tumours and T1 intraoral tumours when considered as radical treatment, and preferable to consider it as a boost for T2 intraoral tumours. Surface mould brachytherapy results in excellent organ and function preservation.